Konsep Riba Dalam Ekonomi Islam : Studi Literatur - Alsa Apriliansa; Erina Rospajarika R; Amanda Putri Aprilia; Putri Inayah; Irfan Saefuloh; Abdul Baehaki (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2026)
This study seeks to critically examine the concept of riba within the framework of Islamic economics through a comprehensive literature review aimed at clarifying its definition, characteristics, and implications for economic and financial systems. The study is motivated by the ongoing debate surrounding the practice of riba and its relevance to contemporary economic activities, particularly within interest-based financial systems. Data were collected through a systematic documentation process involving primary and secondary sources, including the Qur'an, Hadith, Islamic economics literature, books, and relevant scholarly articles. The analysis identified five major themes: riba as a form of economic injustice, riba as a mechanism of economic exploitation, the classification of riba in Islamic jurisprudence, its relevance in modern financial systems, and its relationship to efforts aimed at achieving social welfare. The findings indicate that the prohibition of riba encompasses not only normative and religious dimensions but also socio-economic values that contribute to reducing inequality and promoting the development of a more equitable economic system.